Autoryzacja w praktyce nowych mediów w dobie kryzysu systemu prawa prasowego - Skrzypczak, Jędrzej (Wydawnictwo Naukowe WNPiD UAM, 2012)
Assuming that a crisis infers the collapse of old values while the new ones to replace them have not developed yet, one can ponder whether we are witnessing a crisis of press law in Po- land or not. Taking into consideration the gravity and scope of criticism of the current press law act and the repeated attempts to alter the existing legal status quo, it could be said that we are facing a permanent crisis in the press law system in Poland, and, consequently, of the whole media policy. The paper tries to verify this hypothesis on the example of one of the ele- ments of the press law, namely that of authorization.
Authorization in the Use of New Media during a Period of Crisis in the Press Law System
Keywords: autoryzacja; prawo prasowe; nowe media